2022
DOI: 10.17533/udea.ikala.v27n1a07
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of the Tap/Trill Contrast in the Bilingual Creole-Spanish Community of the Archipelago of San Andres, Colombia

Abstract: This study examines the segmental duration of non-vibrant rhotics in a language contact scenario in the Western Caribbean, where an English-based Creole co-exists with Spanish: The Archipelago of San Andres, Colombia. The unexplored phenomenon of the neutralization of the tap/trill contrast merits a thorough analysis to examine the effects of language contact in this Creole-Spanish bilingual population. To do this, the segmental duration of 619 non-vibrant, intervocalic taps and trills were compared in three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous research has identified several formant frequencies as the best acoustic predictors for distinguishing zero-occlusion rhotic production in the linguistic varieties of the Archipelago of San Andres (Restrepo-Ramos, 2021). Precisely, the manner of articulation of these allophonic variants has been examined in detail in a previous study (Restrepo-Ramos, 2021) and it has been determined to conform to an approximant realization in both taps and trills produced with no lingual closures in Raizal Spanish. Thus, both the bilingual varieties and the contact languages are characterized by approximant rhotics when no lingual closure is present.…”
Section: Rhotic Variation and Sound Changementioning
confidence: 99%
“…Previous research has identified several formant frequencies as the best acoustic predictors for distinguishing zero-occlusion rhotic production in the linguistic varieties of the Archipelago of San Andres (Restrepo-Ramos, 2021). Precisely, the manner of articulation of these allophonic variants has been examined in detail in a previous study (Restrepo-Ramos, 2021) and it has been determined to conform to an approximant realization in both taps and trills produced with no lingual closures in Raizal Spanish. Thus, both the bilingual varieties and the contact languages are characterized by approximant rhotics when no lingual closure is present.…”
Section: Rhotic Variation and Sound Changementioning
confidence: 99%